Eficácia da escada analgésica da organização mundial da saúde (OMS) em um modelo de síndrome dolorosa induzida por paclitaxel em ratos - Pinheiro, Kelly de Vargas (2014)
Paclitaxel use in cancer is limited by a painful syndrome characterized by acute and chronic phases and by the lack of efficacious therapies. Thus, we assessed the efficacy of analgesics used in the World Health Organization (WHO) ladder for a cancer pain relief in a model of paclitaxel-induced pain syndrome (P-IPS). Hyperalgesia was measured with von Frey filaments. P-IPS was induced in rats by four injections of paclitaxel on alternate days. The acute and chronic phases were assessed 24 h and 15 days after the first injection, respectively. Rats were treated orally with vehicle, acetaminophen (step 1 of the ladder), codeine alone or plus acetaminophen (step 2) and morphine (step 3) after acute or chronic phases assessment. Acetaminophen, codeine and morphine were equi-efficacious in reversing the acute phase of the P-IPS, but opioids were more potent than acetaminophen. Codeine plus acetaminophen had similar efficacy and potency when administered together, but produced longer-lasting effect. The repeated treatment with paclitaxel also led to a marked hyperalgesia in the chronic phase of the painful syndrome. Acetaminophen, codeine and morphine partially reversed chronic phase of P-IPS, losing their efficacy and, in the case of codeine, potency when compared to acute phase. However, the administration acetaminophen with codeine increased the potency and the efficacy of the opioid, producing a long-lasting anti-hyperalgesic effect. Together, analgesics of WHO ladder are capable of reverting both acute and chronic phases of P-IPS, with codeine plus acetaminophen presenting more potent, efficacious and long-lasting effect. Thus, WHO analgesics ladder could also be useful to treat P-IPS.